Morphological development of the human fetal striatum during the second trimester. (25th January 2022) - Tian, Mimi; Xu, Feifei; Xia, Qing; Tang, Yuchun; Zhang, Zhonghe; Lin, Xiangtao; Meng, Haiwei; Feng, Lei; Liu, Shuwei
Abstract: The morphological development of the fetal striatum during the second trimester has remained poorly described. We manually segmented the striatum using 7.0-T MR images of the fetal specimens ranging from 14 to 22 gestational weeks. The global development of the striatum was evaluated by volume measurement. The absolute volume ( V abs ) of the caudate nucleus (CN) increased linearly with gestational age, while the relative volume ( V rel ) showed a quadratic growth. Both V abs and V rel of putamen increased linearly. Through shape analysis, the changes of local structure in developing striatum were specifically demonstrated. Except for the CN tail, the lateral and medial parts of the CN grew faster than the middle regions, with a clear rostral–caudal growth gradient as well as a distinct "outside–in" growth gradient. For putamen, the dorsal and ventral regions grew obviously faster than the other regions, with a dorsal–ventral bidirectional developmental pattern. The right CN was larger than the left, whereas there was no significant hemispheric asymmetry in the putamen. By establishing the developmental trajectories, spatial heterochrony, and hemispheric dimorphism of human fetal striatum, these data bring new insight into the fetal striatum development and provide detailed anatomical references for future striatal studies.